RTHP-35. RE-IRRADIATION USING PULSED REDUCED DOSE RATE RADIATION THERAPY IN PATIENTS WITH GRADE 2 GLIOMAS. (11th November 2019) - Harari, Colin; Burr, Adam; Ian Robins, H; Howard, Steven
Abstract: BACKGROUND: The time course of progressive grade 2 glioma can span nearly a decade. However, much less is known about re-irradiation in this cohort than in high grade patients. Pulsed reduced dose rate (PRDR) radiation therapy is a method of radiation delivery, which may spare normal tissues by slowing the rate of radiation delivery to allow repair. METHODS: We identified consecutive patients from an institutional database initially diagnosed with grade 2 glioma from 2001 to 2017 who underwent pulsed reduced dose rate radiation therapy. Radiation was delivered in 20 cGy pulses every three minutes, most commonly with a 3D conformal, three field technique, encompassing gross disease with a 1–2 cm margin. Kaplan Meier method was utilized to analyze patient outcomes. RESULTS: 35 patients with grade 2 glioma were identified. The median survival from the date of the first surgery was 103 months (95% CI 78–129 mo). 71% underwent at least a second resection and 86% of patients receiving chemotherapy. 80% of patients underwent transformation to grade 3 (51%) or grade 4 (29%) glioma. Overall survival from PRDR was 9.8 months (95% CI 4.5–14.5mo) and progression free survival was 6.2 months (95% CI 5.1–7.4) in all patients. Overall response rate was 37%. In patients who remained grade 2 histology, overall survival was 13.3 months and two patients remain disease free at 83 and 34 months with overall response of 71%. Four seizures were documented, otherwise treatment was well tolerated. CONCLUSIONS: Progressive grade 2 glioma can progress and evolve over nearly the course of a decade. This study demonstrates the efficacy of re-irradiation in prolonging survival in these patients by delaying progression. In patients who remain with grade 2 disease, prolonged salvage of their disease appears possible.